Double burden of malnutrition among elderly people in Bangladesh: Evidence from the National Nutrition Surveillance Study - Hasan, Mehedi; Shamim, Abu Ahmed; Hossain, Md. Mokbul; Hanif, Abu Abdullah Mohammad; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S M Mustafizur; Mitra, Dipak Kumar; Haque, Md. Emdadul; Mridha, Malay (Oxford Academic, 2022)
This article was published in Current Developments in Nutrition [Oxford University Press Copyright © Oxford University Press 2020.] and the definite version is available at: https://doi.org/10.1093/cdn/nzaa053_045 The Journal's website is at: https://academic.oup.com/cdn/article/4/Supplement_2/840/5845144